Two new species of Ovitamon Ng & Takeda, 1992 (Crustacea: Brachyura: Potamidae) from the Philippines - Manuel-Santos, Marivene R.; Ng, Peter K. L. (Zootaxa, 2013)
Two new species of potamid freshwater crabs of the genus Ovitamon Ng & Takeda, 1992, are described from the islands of Mindoro and Panay, Philippines. The two new species can easily be distinguished from congeners by the morphologies of their carapaces and male first gonopods. Six species of Ovitamon are now known from the islands of central and western Philippines.